International income risk-sharing and the global financial crisis of 2008–2009 - Balli, Faruk; Basher, Syed Abul; Balli, Hatice Ozer (Journal of Banking & Finance, 2013)
We examine the impact of the global financial crisis on the degree of international income and consumption risk-sharing among industrial economies using returns on cross-border portfolio holdings (e.g., debt, equity, FDI). We split the returns from the net foreign holdings as receipts (inflows) and payments (outflows) to investigate which of the two sides exhibited the greater resilience for income risk-sharing during the recent crisis. First, we find that debt delivered better risk-sharing than equity, mainly reflecting the deficit deterioration in EMU countries during the post-crisis period. FDI, by contrast, did not correspond to noticeable risk diversification. Second, separating output shocks into positive and negative components reveals that debt holding receipts (equity liability payments) performed better under negative (positive) realizations of the shock variable. Third, the unwinding of capital flows resulted in a sharp fall in income dis-smoothing via the debt liability channel in the new EU countries.